2019
DOI: 10.4314/ijbcs.v12i5.37
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation physico-chimique des eaux des aquifères du Continental Intercalaire / Hamadien et du Continentalsiems Terminal de la région de Zinder (Niger)

Abstract: RESUME L'agriculture et l'élevage constituent les principales activités socio-économiques de la population de la région de Zinder (Niger). Toutefois, ces activités présentent des impacts négatifs sur la qualité des eaux souterraines constituant l'une des principales sources d'approvisionnement en eau de cette population. Cette étude a pour objectif de déterminer la qualité physico-chimique et l'origine de la minéralisation des eaux des aquifères du Continental Intercalaire / Hamadien et du Continental Terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Tese results are similar to those found in the study by Bouteraa and colleagues who showed that groundwater quality is infuenced by geochemical processes (water-rock interaction) and human practices (irrigation) [20]. In addition, the study conducted in the Zinder region of Niger revealed that there are two mechanisms responsible for water mineralization which are soil rainfall and residence time in the aquifer [9]. On the other hand, the distribution of nineteen physicochemical and bacteriological parameters using varimax rotation on the factorial planes (Factor 1-Factor 2), (Factor 1-Factor 3), and (Factor 1-Factor 4) showed that all factors except Factor 1 showed contamination by nitrates which are mainly due to anthropogenic action and are introduced into the subsoil, either by leaching of applied fertilizers or by wastewater discharge.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Tese results are similar to those found in the study by Bouteraa and colleagues who showed that groundwater quality is infuenced by geochemical processes (water-rock interaction) and human practices (irrigation) [20]. In addition, the study conducted in the Zinder region of Niger revealed that there are two mechanisms responsible for water mineralization which are soil rainfall and residence time in the aquifer [9]. On the other hand, the distribution of nineteen physicochemical and bacteriological parameters using varimax rotation on the factorial planes (Factor 1-Factor 2), (Factor 1-Factor 3), and (Factor 1-Factor 4) showed that all factors except Factor 1 showed contamination by nitrates which are mainly due to anthropogenic action and are introduced into the subsoil, either by leaching of applied fertilizers or by wastewater discharge.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, the factorial designs (F1-F2), (F1-F3), and (F1-F4), show a negative correlation with the parameters Fe 2+ , TC and K + . Tis could be due to the heterogeneity of the waters of these aquifers and the low values of these ions recorded, as according to the work of Souley Moussa et al in 2019 [9], out of the nineteen parameters he studied, fve of them do not participate in the constitution of the factorial axes. Similarly, the distribution of physicochemical and bacteriological parameters on the factorial planes (F1-F2), (F1-F3), and (F1-F4) allowed the identifcation of the phenomena at the origin of the mineralization of these groundwater, which are related to soil rainfall and residence time in the aquifer, as well as to agricultural pollution due to the use of nitrogenous fertilizers, and to water-rock contact.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Zeroud groundwater samples had pH values ranging from 6.7 to 7.73, with an average of 7.286, suggesting that the water samples were slightly alkaline and fell within the pH range of (6.5-8.4) recommended for irrigation purposes [89]. These slightly neutral to alkaline values of pH were probably due to the alteration of feldspars and some carbonated minerals [90]. The electrical conductivity (EC) values in the groundwater samples varied significantly from 1514.7 to 5185.9 µS.cm −1 .…”
Section: Groundwater Hydrochemical Propertiesmentioning
confidence: 99%
“…Corresponding author: yayakendabailodiallo@gmail.com, konateahmeda@gmail.com Full Paper DOI: 10.2478/asn-2023-0011 ©2023 Yaya Kenda Baïlo Diallo, Ahmed Amara Konaté, published by Sciendo This work is licensed under the Creative Commons Attribution 3.0 Public License4.4. Hydrogeochemical faciesAnalysis of the chemical results (cation and major anion) by the hydrochemical method that uses the triangular Piper digram shows that groundwater has different facies[25]. Figure15shows the hydrogeochemical facies of the waters of the seven wells on the Piper diagram.…”
mentioning
confidence: 99%